2015
DOI: 10.1007/s00167-015-3682-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soft tissue laxity of the knee joint on limb alignment correction in open-wedge high tibial osteotomy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
159
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(170 citation statements)
references
References 34 publications
8
159
2
1
Order By: Relevance
“…We suppose that patients with severe varus deformity, as evidenced by high correction and HKA angles, have medial soft tissue tightness. Previous studies reported that the preoperative degree of soft tissue laxity in the knee joint was significantly related to the degree of postoperative alignment correction . Based on this finding, we consider that opening from the anteromedial direction is more likely to result in insufficient postoperative correction in cases in which the medial soft tissue is tight due to severe varus deformity.…”
Section: Discussionsupporting
confidence: 52%
“…We suppose that patients with severe varus deformity, as evidenced by high correction and HKA angles, have medial soft tissue tightness. Previous studies reported that the preoperative degree of soft tissue laxity in the knee joint was significantly related to the degree of postoperative alignment correction . Based on this finding, we consider that opening from the anteromedial direction is more likely to result in insufficient postoperative correction in cases in which the medial soft tissue is tight due to severe varus deformity.…”
Section: Discussionsupporting
confidence: 52%
“…JLCA and min‐JSW were measured for they were evaluation indicators of the relaxation of supporting structures and degeneration of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Among radiologic parameters, FBA, mMDFA, and DFVRA were the morphological indicators of the femur, MPTA was the morphological indicator of the tibia, and min‐JSW and JLCA were the indicators of cartilage and soft tissue. All angles were showed in Figure .…”
Section: Methodsmentioning
confidence: 97%
“…8,17,20,46,47 Meanwhile, Marti et al 48 proposed that the correction angle should be planned according to the cartilage width on the standing whole-leg radiograph. If onethird of the thickness of the medial cartilage was lost, the mechanical axis was planned to pass lateral to the center of the knee at the 10% position.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with the contention that postoperative valgus alignment with medial laxity can be aggravated in the standing position. 8,47,49,50 The combined CTbased and image-free navigation system enabled acquisition of an accurate osteotomy and simultaneous control of the FTA and TPS in both planes. However, the discrepancy in the medial opening between the supine and standing positions remained.…”
Section: Discussionmentioning
confidence: 99%